Superconducting high-field wigglers and wave length shifters in Budker INP - Batrakov, A.M.; Bekhtenev, E.A.; Borovikov, V.M.; Djurba, V.K.; Fedurin, M.G.; Repkov, V.V.; Karpov, G.V.; Khruschev, S.V.; Kulipanov, G.N.; Kuzin, M.V.; Lev, V.K.; Mezentsev, N.A.; et al. (Вопросы атомной науки и техники, 2001)
Several high-field superconducting wigglers (SCW) and wavelength shifters (WLS) are fabricated in the Budker INP for generation of synchrotron radiation. Three-pole WLS with the magnetic field of 7.5 T are installed on LSU‑CAMD and BESSY-II storage rings for shifting the radiation spectrum. WLS with the field of 10.3 T will be used for generation of slow positrons on SPring-8. Creation of a 13-pole 7 T wiggler for the BESSY-II and 45-pole 3.5 T wiggler for ELETTRA now is finished. The main characteristics, design features and synchrotron radiation properties of SCW and WLS created in the Budker INP are presented in this article.